2017
DOI: 10.1016/j.bmcl.2017.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Escape from adamantane: Scaffold optimization of novel P2X7 antagonists featuring complex polycycles

Abstract: The adamantane scaffold, despite being widely used in medicinal chemistry, is not devoid of problems. In the recent years we have developed new polycyclic scaffolds as surrogates of the adamantane group with encouraging results in multiple targets. As an adamantane scaffold is a common structural feature in several P2X7 receptor antagonists, herein we report the synthesis and pharmacological evaluation of multiple replacement options of adamantane that maintain a good activity profile. Molecular modeling studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…There is a problem, however, concerning the many polymorphic forms of the human P2X7R, as care must be taken in identifying those patients that would most benefit by the available antagonists, as different antagonists are not always effective agents at some of the polymorphic types (see [ 210 ]). There is an explosion of interest in developing centrally penetrant P2X7R antagonists and their therapeutic explorations in clinical trials [ 211 213 ]. The relation between inflammation elicited by P2X7R activation and the immune system needs further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…There is a problem, however, concerning the many polymorphic forms of the human P2X7R, as care must be taken in identifying those patients that would most benefit by the available antagonists, as different antagonists are not always effective agents at some of the polymorphic types (see [ 210 ]). There is an explosion of interest in developing centrally penetrant P2X7R antagonists and their therapeutic explorations in clinical trials [ 211 213 ]. The relation between inflammation elicited by P2X7R activation and the immune system needs further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Amantadine and memantine are extremely simple adamantane derivatives which were among the first pharmaceutical hits in the 1960s, and are used to ameliorate side-effects of Parkinson's medication levodopa and symptoms of Alzheimer's, respectively. Since AstraZeneca's initial research into adamantyl-based compounds as P2X 7 antagonists (1; Figure 3) for treatment of chronic inflammatory disease [49], academic research groups have shown the use of trifluoroadamantanes (SMW139) [50], cubanes (2; Figure 3), carboranes (3; Figure 3) [48,49], and bisnoradamantane [51] to antagonize the same receptor [52,53].…”
Section: Schubert and Coworkers Have Recently Designed A Series Of Ce...mentioning
confidence: 99%
“…Early hit-to-lead studies have suggested that removing or flattening the adamantane to a simpler cycloalkane, to reduce lipophilicity and molecular weight, is detrimental to potency suggesting a large three-dimensional structure is central to potent P2X 7 R antagonism . We, and others, have confirmed this notion by substituting the adamantane of lead benzamide 1 with a variety of polycyclic cages (from cubane to carborane) and found that the larger polycyclic volume was crucial for P2X 7 R antagonism . Unfortunately, the larger polycycles also result in more lipophilic compounds.…”
mentioning
confidence: 99%